Routine screening for suicidal intention in patients with cancer1. Issue 11 (22nd July 2013) - Leung, Yvonne W.; Li, Madeline; Devins, Gerald; Zimmermann, Camilla; Rydall, Anne; Lo, Chris; Rodin, Gary
Abstract: Objectives: Suicide rates are elevated in individuals with cancer, although suicidal intention is not typically assessed in cancer centers. We evaluated in a large comprehensive cancer center the utility of an electronic Distress Assessment and Response Tool (DART), in which suicidal intention is assessed with a single item. Methods: Patients attending cancer clinics completed DART as part of routine care. DART includes measures of physical symptoms, depression, anxiety, social difficulties, and practical concerns. Medical variables were obtained from the Princess Margaret Cancer Registry, the data warehouse of cancer patient statistics. A Generalized Estimating Equation (GEE) model was used to assess factors associated with suicidal intention. Results: Between September 2009 and March 2012, 4822/5461 patients (88.3%) who completed DART consented to the use of their data for research. Amongst the latter, 280 (5.9%) of the 4775 patients who answered the question reported suicidal ideation, which was related to physical and psychological distress, and social difficulties ( p s < 0.0001). Amongst those with ideation who responded to the intention question, 20/186 (10.8%) reported suicidal intention. Of respondents with more severe suicidal ideation, 12/49 (24.5%) reported suicidal intention. Using a GEE model, suicidal intention in those with ideation was significantly associated with male sex, difficulty making treatment decisions, and with everyday living concerns. Conclusions: Suicidal ideation is reported on an electronic distress screening tool (DART) by almost 6% of cancer patients, of whom almost 11% report suicidal intention and 33% decline to indicate intention. DART demonstrated utility in identifying patients who may be at highest risk of completed suicide and who require urgent clinical assessment. Copyright © 2013 John Wiley & Sons, Ltd.